MgFe2O4/Biochar Composites for Visible-Light Photo-Fenton Treatment of Azo Dyes: Material Optimization Assisted by Decision Tree Analysis - Jandira Leichtweis; Ana C. Ferreira Piazzi Fuhr; Guilherme Luiz Dotto; Luis G. Ramírez Mérida; Elvis Carissimi; Mathias Ulbricht; Salatiel Wohlmuth Da Silva (Water, Air, & Soil Pollution, 2026)
The increasing release of synthetic dyes into aquatic systems represents a significant environmental concern due to their persistence, toxicity, and resistance to conventional treatment processes. In this study, MgFe 2 O 4 /biochar composites derived from waste coffee grounds were developed as sustainable materials for the removal of organic pollutants from water via a heterogeneous photo-Fenton process. The materials were synthesized and characterized using XRD, FT-IR, SEM, EDS, and band gap analysis, revealing that the incorporation of biochar enhances surface functionality and promotes efficient electron transfer. The performance of the composites was evaluated for the degradation of tartrazine (TZ) and methyl orange (MO), two widely used azo dyes frequently detected in wastewater. Among the tested compositions, MFO1BC1 achieved complete color removal (100%) of both dyes within 60 min, significantly outperforming pure MgFe 2 O 4 . This improvement can be attributed to the synergistic interaction between MgFe₂O₄ and biochar, which may contribute to improved active-site accessibility and could facilitate charge separation, thereby enhancing the photo-Fenton treatment efficiency. A decision tree (DT) model was used to assist in the interpretation of the experimental data and selection of the optimal composite composition. Reusability tests confirmed the stability of the catalyst over eight cycles, indicating its practical applicability for wastewater treatment systems. Radical scavenging experiments identified •OH and O 2 •⁻ as the main species possibly responsible for pollutant degradation. This study provides new insights into the use of biochar-based composites for environmental remediation, highlighting a low-cost, sustainable, and efficient strategy for the treatment of dye-contaminated water, with potential implications for large-scale wastewater management and pollution control.